How many peripersonal spaces?. (April 2015) - de Vignemont, F.; Iannetti, G.D.
Abstract: Several studies in humans and non-human primates have explored and characterised the features of the cortical representation of the portion of space immediately surrounding the body – the peripersonal space. In this paper we ask the following question: is it legitimate to assume that there is a single representation of peripersonal space? This issue has rarely been addressed in the literature, leading to much confusion, especially when one compares results reported in social psychology and in cognitive neuroscience. Indeed, studies in both fields explore and refer to more or less the same portion of space, but the terminology used to describe it differs greatly. Therefore, the definition of this portion of space immediately surrounding the body has remained quite vague, allowing for many variations. Here, we propose a dual model of peripersonal space, based on a clear functional distinction between bodily protection and goal-directed action . We argue that the two functions of peripersonal space require distinct sensory and motor processes that obey different principles. Furthermore, we highlight that the effects of anxiety and tool use on peripersonal space provide empirical support to our distinction. Highlights: There is more than one representation of peripersonal space. Protective peripersonal space and working peripersonal space obey different sensory, motor and spatial principles. Anxiety reduces the extension of working space while extending protective space. Tool use extends the working space but has no effect on protective space.